Prolactinoma: A Condition Associated with Hypoadiponectinemia - de Assunção Alves Rodrigues, L. F.; Campos, S.M. S.; Miranda, P.A. C.; Bizzi, M. F.; Sales do Amaral, P. H.; Giannetti, A. V.; Ribeiro-Oliveira, A. (Hormone and Metabolic Research, 2012)
Prolactinomas are prolactin-secreting neoplasias accounting for 40% of the pituitary adenomas. Much is known about the effects of prolactinomas on the reproductive system, but few data are yet available regarding their induced changes on metabolism. This study was aimed at evaluating patients with prolactinomas for insulin resistance and adiponectinemia. Forty patients with prolactinoma were allocated to 2 different groups according to disease control: 20 with uncontrolled disease (UPRL) and 20 with controlled disease in the last 6 months (CPRL). Forty healthy individuals (CG) matched for age, sex, and body mass index were taken as controls. Patients with prolactinoma were compared both as a one group and according to disease control with CG. All subjects were evaluated for waist/hip ratio (WHR), blood pressure, lipid profile, fasting glucose, homeostasis assessment model of insulin resistance (HOMAIR), and adiponectin. Patients with prolactinomas (UPRL+CPRL) showed higher insulin (p<0.05) and HOMAIR (p<0.05), alongside with lower adiponectin levels (p<0.01) than matched controls. When UPRL was compared to CPRL and CG, UPRL was disclosed as a subgroup of significant altered metabolic profile as related to WHR (p<0.01 for comparisons), high-density lipoprotein cholesterol (p<0.05 for comparisons), triglycerides (p<0.05 for comparisons), HOMAIR (p<0.05 and p<0.01, respectively), and adiponectin (p<0.01 for comparisons). All these metabolic abnormalities, except hypoadiponectinemia (p<0.01), were not observed in CPRL. These data suggest that prolactinomas are associated with hypoadiponectinemia, which is further exacerbated in uncontrolled patients when insulin resistance is also prominent.
Keywords: adiponectin; hyperlipidemia; HOMAIR; insulin resistance; prolactin